Priority allocation of pandemic influenza vaccines in Australia – Recommendations of 3 community juries. Issue 2 (8th January 2021) - Degeling, C.; Williams, J.; Carter, S.M.; Moss, R.; Massey, P.; Gilbert, G.L.; Shih, P.; Braunack-Mayer, A.; Crooks, K.; Brown, D.; McVernon, J.
Abstract: Background: Pandemic planning has historically been oriented to respond to an influenza virus, with vaccination strategy being a key focus. As the current COVID-19 pandemic plays out, the Australian government is closely monitoring progress towards development of SARS-CoV2 vaccines as a definitive intervention. However, as in any pandemic, initial supply will likely be exceeded by demand due to limited manufacturing output. Methods: We convened community juries in three Australian locations in 2019 to assess public acceptability and perceived legitimacy of influenza pandemic vaccination distribution strategies. Preparatory work included literature reviews on pandemic vaccine allocation strategies and on vaccine allocation ethics, and simulation modelling studies. We assumed vaccine would be provided to predefined priority groups. Jurors were then asked to recommend one of two strategies for distributing remaining early doses of vaccine: directly vaccinate people at higher risk of adverse outcomes from influenza; or indirectly protect the general population by vaccinating primary school students, who are most likely to spread infection. Results: Thirty-four participants of diverse backgrounds and ages were recruited through random digit dialling and topic-blinded social media advertising. Juries heard evidence and arguments supporting different vaccine distribution strategies, and questioned expert presenters. All three community juries supported prioritising school children for influenza vaccination (aiming for indirect protection), one by 10–2 majority and two by consensus. Justifications included that indirect protection benefits more people and is likely to be more publicly acceptable. Conclusions: In the context of an influenza pandemic, informed citizens were not opposed to prioritising groups at higher risks of adverse outcomes, but if resources and epidemiological conditions allow, achieving population benefits should be a strategic priority. These insights may inform future SARS-CoV-2 vaccination strategies.